Implementasi Kaidah Fikih “Al-Ḍarūrāt Tubīḥu Al-Maḥẓūrāt” dalam Program Vaksinasi di Indonesia Menggunakan Vaksin AsrtaZeneca - Muamar, Muhammad; Basuki, Samudra Prihatin Hendra (Alhamra Jurnal Studi Islam, 2023)
This research will reveal the use of the AstraZeneca vaccine which has been used by the Indonesian people with the "al-á¸arÅ«rÄt tubÄ«á¸¥u al-maá¸¥áº“Å«rÄtâ€ fiqh rule approach. This study is different from other researchers in the approach used as a reason for the ability to use vaccines as an effort of the government to create Herd Immunity in the context of preventing the Covid-19 virus. Although this vaccine is forbidden, researchers see that other gaps can reveal the use of vaccines from Sharia reviews. This study aims to find answers to existing problems regarding the halal status of the AstraZeneca vaccine used by the government in the vaccination program in Indonesia recently. This research is qualitative research where data is produced and presented descriptively and includes library research (library research) taken by analyzing the content of the contents of related literature. In this study, a qualitative study was conducted by obtaining data and presenting it descriptively and including literature research which was carried out by analyzing the content of the related data. The normative method is used in the MUI Fatwa Number: 14 of 2021 concerning the Law on the Use of the AstraZeneca Product Covid-19 Vaccine. This research yields an indication of the urgent need for the use of the AstraZeneca vaccine based on the MUI Fatwa regarding the use of the Covid-19 vaccine which, if not consumed, is categorized as al-á¸arÅ«rÄh which threatens life or limb.